An Assessment on Activities of Regional Development Agencies in Turkey - Yavuz Tiftikcigil, Burcu (International Journal of Economics and Financial Issues, 2015)
Regional development policies became a current issue within a totally new scope with the increasing importance of local activities by the 1990s. During this period, states having a national perspective on development were replaced by 'regional development agencies' within the framework of newly emerging understanding of ‘governance'. Regional development policies in Turkey were transformed from centralization to decentralization with the process of membership to the European Union. The “Development Agencies” emerging from this process were established in 26 Level 2 Regions in Turkey, starting from 2006. In this context, this study is designed to examine the activities of Development Agencies, established within 26 Level 2 Regions in Turkey, based on their activity reports, and to identify the compliance of these activities with tasks and responsibilities of the Agencies. This study uses the ‘Call for Proposals' mechanism as an activity of the agencies. Keywords: Development Agency; Activity Report; Regional Development; Decentralization; Governance JEL Classifications: O110; R110; R580; R190